The Urgency of Reforming Indonesian Arbitration Law From a Paradigmatic Perspective - Taufiqurrahman, Taufiqurrahman; Endarto, Budi (Arena Hukum, 2024)
Over time, a growing interest has emerged among various stakeholders in reforming Indonesia’s Law No. 30 concerning arbitration and alternative dispute resolution. The existing Arbitration Law is increasingly viewed as outdated and misaligned with global developments in arbitration. While the need to update Indonesia’s Arbitration Law is evident, it is essential to approach this reform with a well-defined direction rather than merely following current trends without purpose. This study explores the foundational paradigms that could guide Indonesia’s Arbitration Law reform. The study employs a normative legal research method, utilising both statutory and conceptual approaches. The findings suggest that the universalistic particularism paradigm could serve as a basis for reforming Indonesian Arbitration Law. It is recommended that the current Arbitration Law be maintained for domestic arbitration, while the UNCITRAL Model Law on International Commercial Arbitration should be adopted for international arbitration matters.